Pharmacognostical, phytochemical and anthelmintic activity of Polygonum muricatum - Goswami, Priyanka; Islam, Rajibul; Khongmalai, Everlasting; Sarkar, Bapi Ray; Sen, Saikat; Choudhury, Ananta; Dey, Biplab Kumar (Creative Pharma Assent, 2018)
Polygonum muricatum is widely used by the local people of Meghalaya for anthelmintics. An attempt has been made to evaluate the pharmacognostical, preliminary phytochemical and pharmacological parameters of leaves of Polygonum muricatum. The physicochemical constants like moisture content, ash values such as total ash, acid insoluble ash and water soluble ash, extractive values such as water soluble extractive value and alcohol soluble extractive value were determined. The extract obtained by successive solvent extraction was subjected to preliminary phytochemical analysis to find out the presence of compounds. The plant Polygonum muricatum leaves were extracted with the solvent benzene, acetone, ethanol and water by soxhlet apparatus method. The extract was evaluated for anthelmintic activity with Indian earthworm. Ethanol extract of the plant Polygonum muricatum has shown the significant activity.